Design, Synthesis, and Biological Evaluation of Novel Thiazolidinone-Containing Quinoxaline-1,4-di-N-oxides as Antimycobacterial and Antifungal Agents - Zhang, Heying; Zhang, Jie; Qu, Wei; Xie, Shuyu; Huang, Lingli; Chen, Dongmei; Tao, Yanfei; Liu, Zhenli; Pan, Yuanhu; Yuan, Zonghui (Frontiers in Chemistry, 2020)
Tuberculosis and fungal infections can pose serious threats to human health. In order to find novel antimicrobial agents, 26 novel quinoxaline-1,4-di-N-oxides containing a thiazolidinone moiety were designed and synthesized, and their antimycobacterial activities were evaluated. Among them, compounds 2t, 2u, 2y, and 2z displayed the most potent antimycobacterial activity against Mycobacterium tuberculosis strain H37Rv (minimal inhibitory concentration [MIC] = 1.56 μg/mL). The antifungal activity of all the compounds was also evaluated against Candida albicans, Candida tropicalis, Aspergillus fumigatus, and Cryptococcus neoformans. Compounds 2t, 2u, 2y, and 2z exhibited potential antifungal activities, with an MIC between 2 and 4 μg/mL. Comparative molecular field analysis (CoMFA: q2 = 0.914, r2 = 0.967) and comparative molecular similarity index analysis (CoMSIA: q2 = 0.918, r2 = 0.968) models were established to investigate the structure and antimycobacterial activity relationship. The results of contour maps revealed that electronegative and sterically bulky substituents play an important role in the antimycobacterial activity. Electronegative and sterically bulky substituents are preferred at the C7 position of the quinoxaline ring and the C4 position of the phenyl group to increase the antimycobacterial activity. Additionally, more hydrogen bond donor substituents should be considered at the C2 side chain of the quinoxaline ring to improve the activity.